Tourism & Covid-19 (Coronavirus Impact Inventory to Tourism Stakeholders in North Sumatera) - Sinulingga, Samerdanta (Budapest International Research and Critics University, 2021)
This research aims to map the problems posed by COVID-19 to tourism conditions in North Sumatra to near the conditions of zero tourism. To date, no effort can be made by the tourism industry to solve the problem of COVID-19, only await the government in tackling it. From The study it was found that the keys indicators in measuring the impact of COVID-19 on tourism are; The impact on economic, social, environmental also the assessment through time, change, and quality of tourism. A new finding is that the impact of tourism can also be assessed through time, change, and quality of tourism. This data is using qualitative methods through in-depth interviews with four major stakeholders of the tourism industry; management of tourist destinations, tour agencies, accommodation, and transportation services. The results of this study illustrated the chronology of tourism activities to zero tourism situation, from the four main stakeholders, which in charge of transportation services and tour agency was the most affected stakeholder and could not operate in the time of COVID-19. The results of the study can be a formula in formulating a strategic tourism management policy during the outbreak until the tourism activity can be normal again.